Autologous Hematopoetic Stem Cell Transplantation as An Intensive Consolidation Therapy for Adult Patients in Remission from Acute Myeloid Leukemia - Genadieva-Stavrik, Sonja G; Pivkova, Alexandra; Stojanoski, Zlate; Krstevska balkanov, Svetlana; Georgievski, Borche (American Society of Hematology, 2010)
Abstract Abstract 4595 Despite advances in our understanding of its pathogenesis, acute myeloblastic leukemia remains difficult to treat. Although initial complete remission can be achieved in a high percentage of patients, relapse occurs in 70–80% of the patients. Two main approaches have been the attempt to eradicate the leukemic clonal cells population via chemotherapy with or without autologous stem cell rescue or to pursue a combined approach using an antileukemic therapy combined with an antileukemic immune response via allogeneic bone marrow transplantation. Autologous transplantation compares favorably against allogeneic bone marrow transplant in several ways. Autologous transplantation can be used as a consolidation therapy in the older population, and lack of a matched donor does not preclude the patients from this treatment. We report a retrospective analysis on 48 patients diagnosed with de novo AML, who did not have an available histocompatible donor, and who underwent autologous transplantation between years 2000–2009 at the University hematology Clinic, Skopje, Macedonia. All patients had ECOG score 1 or less. The patient's age ranged from 17 to 65 years with the median age 41 years. There were 26 males and 22 females. For stem cell mobilization patients received chemotherapy or chemotherapy plus G-CSF. The preparative chemotherapy regimen prior to autologous transplantation consisted of BuCy in 24 patient, BEAM in 22 and BuCyMel was used in the remaining 2 patients. We used bone marrow as primary source of stem cells in 18 patients, and peripheral blood stem cells in remaining 30 patients. The five years overall survival was 52% and the 5 years disease progression free survival were 42%. We analyzed sever factors that can influence the overall survival and the disease free survival such as: age, disease status, stem cell source, chemotherapy regiments prior to transplantation, conditioning regiments, number of mobilized stem cells. Advanced age and bone marrow stem cell source seems to be more influent factors. We report that the clinical results of autologous hematopoietic stem cell transplantation are sufficiently encouraging to warrant future trials that include autologous transplantation as an option for appropriately selected patients with AML in CR1. We conclude that autologous hematopoietic stem cell transplantation is a reasonable and save intensive consolidation for patients with acute myeloblastic leukemia who do not have a suitable HLA–matched donor. Disclosures: No relevant conflicts of interest to declare.